Orthogonal moments for determining correspondence between vessel bifurcations for retinal image registration. Issue 3 (May 2015) - Patankar, Sanika S.; Kulkarni, Jayant V.
Highlights This paper presents an algorithm for registration of retinal images using orthogonal moment invariants as features. As orthogonal moments are invariant to translation, rotation and scale (TRS); moment invariants features around a vessel bifurcation are unaltered due to TRS and are used to determine the correspondence between reference and test retinal images. The TRS in test retinal image with respect to reference retinal image is estimated using Similarity transformation. The test retinal image is aligned with reference retinal image using the estimated registration parameters. The experimentation is carried out on 4 databases as DRIVE, STARE, VARIA and database provided by local government hospital.